Association between markers of glucose metabolism and risk of colorectal cancer. Issue 6 (27th June 2016) - Xu, Jinming; Ye, Yao; Wu, Han; Duerksen-Hughes, Penelope; Zhang, Honghe; Li, Peiwei; Huang, Jian; Yang, Jun; Wu, Yihua; Xia, Dajing
Abstract : Objectives: Independent epidemiological studies have evaluated the association between markers of glucose metabolism (including fasting glucose, fasting insulin, homeostasis model of risk assessment-insulin resistance (HOMA-IR), glycated haemoglobin (HbA1c) and C peptide) and the risk of colorectal cancer (CRC). However, such associations have not been systematically analysed and no clear conclusions have been drawn. Therefore, we addressed this issue using a meta-analysis approach. Design: Systematic review and meta-analysis. Data sources: PubMed and EMBASE were searched up to May 2015. Primary and secondary outcome measures: Either a fixed-effects or random-effects model was adopted to estimate overall ORs for the association between markers of glucose metabolism and the risk of CRC. In addition, dose–response, meta-regression, subgroup and publication bias analyses were conducted. Results: 35 studies involving 25 566 patients and 5 706 361 participants were included. Higher levels of fasting glucose, fasting insulin, HOMA-IR, HbA1c and C peptide were all significantly associated with increased risk of CRC (fasting glucose, pooled OR=1.12, 95% CI 1.06 to 1.18; fasting insulin, pooled OR=1.42, 95% CI 1.19 to 1.69; HOMA-IR, pooled OR=1.47, 95% CI 1.24 to 1.74; HbA1c, pooled OR=1.22, 95% CI 1.02 to 1.47 (with borderline significance); C peptide, pooled OR=1.27, 95% CI 1.08 to 1.49). Subgroup analysis suggested that a higher HOMA-IR value was significantly associated with CRC risk in all subgroups, including gender, study design and geographic region. For the relative long-term markers, the association was significant for HbA1c in case–control studies, while C peptide was significantly associated with CRC risk in both the male group and colon cancer. Conclusions: The real-time composite index HOMA-IR is a better indicator for CRC risk than are fasting glucose and fasting insulin. The relative long-term markers, HbA1c and C peptide, are also valid predictors for CRC risk. Considering the included case–control studies in the current analysis, more cohort studies are warranted to enhance future analysis.